2016
DOI: 10.1016/j.simyco.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus section Nidulantes (formerly Emericella): Polyphasic taxonomy, chemistry and biology

Abstract: Aspergillus section Nidulantes includes species with striking morphological characters, such as biseriate conidiophores with brown-pigmented stipes, and if present, the production of ascomata embedded in masses of Hülle cells with often reddish brown ascospores. The majority of species in this section have a sexual state, which were named Emericella in the dual name nomenclature system. In the present study, strains belonging to subgenus Nidulantes were subjected to multilocus molecular phylogenetic analyses u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
137
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(142 citation statements)
references
References 244 publications
5
137
0
Order By: Relevance
“…116 Finally, Aspergillus subgenus Nidulantes section Versicolores contains producers of “Aspergamides”: A. amoenus and A. protuberus , 35 but “Aspergamides” could not be found in any species in section Nidulantes . 130 Further studies will show whether the producing species in these sections of Aspergilli all have stereochemical diversity in their production of these compounds.…”
Section: Fungal Producers Of Prenylated Indole Alkaloidsmentioning
confidence: 99%
“…116 Finally, Aspergillus subgenus Nidulantes section Versicolores contains producers of “Aspergamides”: A. amoenus and A. protuberus , 35 but “Aspergamides” could not be found in any species in section Nidulantes . 130 Further studies will show whether the producing species in these sections of Aspergilli all have stereochemical diversity in their production of these compounds.…”
Section: Fungal Producers Of Prenylated Indole Alkaloidsmentioning
confidence: 99%
“…On the other hand, A. pachycristatus is the only species of the section Nidulantes identified here that has not been reported from clinical samples before. This species was described from Chinese soil, and morphologically also resembles A. nidulans , but the ascospores of A. pachycristatus show thicker crests . The closest related species to A. pachycristatus is A. rugulosus ; however, the latter can be distinguished by the rugulose ornamentation on the convex surface of ascospores; in A. pachycristatus , the ascospore surface is smooth …”
Section: Discussionmentioning
confidence: 97%
“…Another difficulty in identifying cryptic species is the fact that the taxonomy is being continuously updated with new modifications due to the new criteria for fungal nomenclature, synonymisations and new species being constantly described in the current literature . For example, among the species reported in the isolates of this study, three of them ( A. europaeus , A. micronesiensis and A. spelaeus ) were not even described at the moment of their isolation from clinical samples.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on morphological similarities Samson (1979) proposed that A. bisporus described by Kwon-Chung & Fennell (1971) also belongs to section Cervini . However, molecular studies revealed that A. bisporus is distantly related to this section, and belongs to subgenus Nidulantes , section Bispori (Peterson 2000, Peterson, 2008, Peterson et al., 2008, Chen et al., 2016). Udagawa et al.…”
Section: Introductionmentioning
confidence: 99%